Outcomes and benefits of a managerial global mindset: An exploratory study with senior executives in North America and India - Ananthram, Subramaniam; Nankervis, Alan (Wiley Periodicals Inc, 2014)
Globalization and its associated challenges are compelling managers in multinational corporations to develop appropriate skill-sets. An emerging body of research in international management has suggested that meeting this challenge requires the cultivation and development of a managerial global mindset. There has been limited empirical work on the outcomes and benefits of a managerial global mindset and consequently this paper attempts to fill that gap. Based on semi-structured interviews with a total of 56 senior executives of multinational corporations in North America (US and Canada) and India, this study identifies five outcomes of a global mindset with benefits for managers and their organizations. The findings have theoretical implications which are discussed along with their practical applications for multinational corporations, their senior executives, and human resource professionals, with respect to identifying management development programs that assist in the cultivation and nurturing of a global mindset.